PENINGKATKAN HASIL BELAJAR AKTIVITAS RITMIK MELALUI PENDEKATAN FORMASI SENAM JADUL PADA SISWA KELAS III SDN GAJAHMUNGKUR 01 KOTA SEMARANG TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study is to boost the learning outcomes of rhythmic activity with the approach of old school gymnastics formation. The experiment was conducted in the Elementary School Gajahmungkur 01 with research subjects were all students of class III totaled 34 students consisting of 14 male students and 20 female students. Sources of data obtained from the performance and outcomes of student learning, teacher performance in the management of learning, and documents and records obtained from the findings during the conduct of research that is carried out through two phases: the first cycle, and II. Data collection technique using a test observation written test and observation of student activity sheets. The method used is a quantitative and qualitative assessment. The results of this study indicate that increased student learning outcomes in each cycle and achieve success, with the KKM 75 and the percentage of success of achieving the initial target of more than 80%. Based on the results of this study concluded, through the formation of gymnastic old school approach, learning outcomes Gajahmungkur Elementary School third grade 01 in a rhythmic activity increased learning. The results of this study provide a positive impact, especially teachers in developing their teaching skills became more varied and foster creativity in the students' learning physical edukation.